BIOLOGICAL ASPECTS OF MANGROVE CRAB (Scylla serrata) AT THE BELADEN ESTUARY, DOMPAK, TANJUNGPINANG, RIAU ISLANDS - Susiana Susiana; Dedy Kurniawan; Rochmady Rochmady; Isnaini Nurwisti; Bintan Rezky; Febrianti Lestari (SEAMEO BIOTROP, 2024)
Mangrove crab (Scylla serrata) is one of the marine organisms that are of significant economic importance. The habitat is distributed in the coastal areas of Indonesia, within the extensive mangrove ecosystems, such as the estuary of Beladen in Dompak, Tanjungpinang. The Beladen estuary area features a flourishing mangrove ecosystem, which supports a diverse range of crab species, with a particular focus on the populations. Therefore, this study aimed to obtain several aspects of mangrove crab in the Beladen estuary, Tanjungpinang. Sampling by the census method was also carried out once every two weeks from May to June 2022. The results showed that the size composition of mangrove crab had a carapace width (CW) of 70-144 mm. The length-weight relationship reported that female and male exhibited a negative and positive allometric growth pattern (b < 3) and (b > 3), respectively. The proportion of male and female was 63% compared to 37% (sex ratio 1:0.59). The value of gonadal maturity index (GMI) in each size class ranged from 2.6512-7.1445 and 1.8751-6.7979 for male and female mangrove crab. Male and female gonadal maturity levels were predominantly categorized as II and III, indicating that crab with mature gonads was not encountered.